2001
DOI: 10.1023/a:1011622830569
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Chatauret, N. et al., 2001. Mild hypothermia prevents cerebral edema and CSF lactate accumulation in acute liver failure. Metabolic Brain Disease, ABSTRACT Evidence from both clinical and experimental studies demonstrates that mild hypothermia prevents encephalopathy and brain edema in acute liver failure (ALF). As part of a series of studies to elucidate the mechanism(s) involved in this protective effect, groups of rats with ALF resulting from hepatic devascularization were maintained at either 37°C (normoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(3 citation statements)
references
References 23 publications
0
1
0
2
Order By: Relevance
“…However, previous studies showed that hypothermia was associated with increased cerebral lactate clearance [32] and also with reduced intracranial pressure and decreased brain edema [33]. The lactate level and its clearance might be affected by overproduction of lactate from skeletal muscle in PCAS patients with seizures or shivering.…”
Section: Discussionmentioning
confidence: 99%
“…However, previous studies showed that hypothermia was associated with increased cerebral lactate clearance [32] and also with reduced intracranial pressure and decreased brain edema [33]. The lactate level and its clearance might be affected by overproduction of lactate from skeletal muscle in PCAS patients with seizures or shivering.…”
Section: Discussionmentioning
confidence: 99%
“…Умеренная гипотермия пациентов (32-34°С) может предотвращать или контролировать повышение ВЧД у па циентов с ОПН. Данные эффекты были доказаны в экспе риментальных моделях на животных [94,95], возможно, за счет предотвращения развития гиперемии, изменения метаболизма аммиака в головном мозге или глюкозы или комбинации этих механизмов. В то же время эффекты ги потермии у пациентов с ОПН не изучались в РКИ, од нако небольшой подтверждающий их клинический опыт существует [96].…”
Section: лечение осложнений опнunclassified
“…Die hepatische Enzephalopathie ist u. a. durch einen erhöhten serologischen Ammoniakspiegel charakterisiert. Ammoniak kann im Gehirn nur durch Astrozyten verstoffwechselt werden, da sie als einzige Zellen des ZNS mittels Glutaminsynthetase Ammoniak zu Glutamin verstoffwechseln können [8]. Durch eine Überproduktion osmotisch aktiven Glutamins schwellen die Astrozyten zu Gemistozyten an.…”
Section: Info Hepatische Enzephalopathieunclassified